مدخل للهوية المهنية - برناوي, بيه; مدور, مليكة (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى تسليط الضوء عن الهوية المهنية، وذلك من خلال التعرف على الهوية المهنية ومكوناتها ومجالاتها ورتب تشكلها، باعتبار أن الهوية نقطة انطلاق نحو الاستقلالية الضرورية لنمو السوي في المراحل العمرية، كما أنها تعبر عن حالة اختبار وتجريب الأدوار الممكنة والتي تتناسب مع قدرات الفرد واستعداداته وصيرورة ذلك في المستقبل. Abstract: This study aimed to shed light on the professional identity, through the identification of the professional identity, its components, fields and the ranks of its formation, considering that the identity is a starting point towards the independence necessary for the growth of normal in the age stages, and it also expresses the state of testing and experimenting with possible roles that are commensurate with the capabilities of the individual And its preparations and its occurrence in the future.
مقال
Keywords: الهوية –الهوية المهنية –تشكل الهوية المهنية –المراهق; identity - professional identity - form the professional identity – teenager